Assessing (and fixing?) Election Day lines: Evidence from a survey of local election officials. (March 2016) - Ansolabehere, Stephen; Shaw, Daron
Abstract: Despite recent studies that find few people face significant wait times when attempting to vote in U.S. elections, the 2012 election produced numerous anecdotal and journalistic accounts claiming otherwise. This study relies on a national survey of local election officials to systematically ascertain their views about the challenges and successes they had in administering the 2012 general election. Consistent with surveys of voters, most officials report that wait times and lines were minimal. Furthermore, the relative amount of money available to a jurisdiction for election administration was unrelated to the occurrence of these problems, while the presence of more poll workers—especially first-timers—may actually exacerbate them. Highlights: Our survey of local election administrators shows long lines were rare in 2012. Places that experienced long wait times were concentrated in a handful of states. Neither larger election administration budgets nor hiring more workers reduced wait times. Fewer first-time workers did correlate with reduced wait times.